2016
DOI: 10.1186/s13099-016-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in amino acid frequency in CagA and VacA sequences of Helicobacter pylori distinguish gastric cancer from gastric MALT lymphoma

Abstract: Background Helicobacter pylori is a pathogenic bacterium that causes various gastrointestinal diseases. The most common gastric malignancies associated with H. pylori are gastric cancer and lymphoma of mucosa associated lymphoid tissue (MALT). Helicobacter pylori virulence genes, namely cagA and vacA, are known to be associated with malignancy development. Conventionally, cagA and vacA were classified by looking at partial sequences of the genes. However, such genotyping has hardly proven useful predicting dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…(39-41) This finding is partially in agreement with the result obtained by Masahiko et al ., that the Amino acid frequency of gastritis samples seems to be intermediate between gastric cancer and MALT lymphoma samples. (42) In contrast, two Japanese strains (NCTC11637 and NCTC11638) isolated from patients with gastritis do not have any mutations in this region (amino acid residues 428-510) except N467G which was found in all our sequences in regardless to gastroduodenal diseases. (43)…”
Section: Discussionmentioning
confidence: 76%
“…(39-41) This finding is partially in agreement with the result obtained by Masahiko et al ., that the Amino acid frequency of gastritis samples seems to be intermediate between gastric cancer and MALT lymphoma samples. (42) In contrast, two Japanese strains (NCTC11637 and NCTC11638) isolated from patients with gastritis do not have any mutations in this region (amino acid residues 428-510) except N467G which was found in all our sequences in regardless to gastroduodenal diseases. (43)…”
Section: Discussionmentioning
confidence: 76%
“…Characteristics of selected studies A total of 153 articles were collected in the initial search, and nally 10 eligible articles met our criteria and were included in the current analysis [32][33][34][35][36][37][38][39][40][41] . A owchart of the article search strategy and study selection is presented in Fig.…”
Section: Reultsmentioning
confidence: 99%
“…However, the detailed mechanisms of CagA-mediated pathogenicity still remain unknown. In a recent study, we reported the dominant presence of asparagine (N), serine (S), valine (V), and serine (S) at CagA site 314, 594, 684, and 1077, respectively, in strains isolated from gastric cancer when compared with the presence of amino acids in strain 26695, whereas serine (S), leucine (L), valine (V), and threonine (T) were in the majority of strains isolated from MALT lymphoma patients [ 36 ].…”
Section: Cytotoxin-associated Gene a (Caga)mentioning
confidence: 99%